SPATH : An adaptive web-based learning system - Yusof, Norazah; Salim, Aminah; Ahmad, Norbahiah; Samsuri, Paridah; Mohd. Hashim, Siti Zaiton (2000)
Nowadays, more and more learning applications are being developed in Malaysia. Unfortunately the focus has been on multimedia technology and standalone applications. Little has been done on providing applications for web based learning, especially systems that are able to cater to the needs of the learners. Often, students are made to undergo certain modules or topics even though they have already acquired the knowledge because the system has not been able to identify this. In addition, instead of the student, it is the system that controls the learning process and thus, more often than not, the learning environment is not able to provide the student with a meaningful way of acquiring knowledge. This paper aims to describe an adaptive web-based learning engine that will identify the student’s performance using information gathered by the student model. It will then provide the student with suitable learning materials, exercises and questions. This paper also discusses AI techniques used by the adaptive engine.